2016
DOI: 10.1590/1806-9282.62.06.568
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial comparing nasal intermittent positive pressure ventilation and nasal continuous positive airway pressure in premature infants after tracheal extubation

Abstract: Objective:To analyze the frequency of extubation failure in premature infants using conventional mechanical ventilation (MV) after extubation in groups subjected to nasal intermittent positive pressure ventilation (nIPPV) and continuous positive airway pressure (nCPAP). Method: Seventy-two premature infants with respiratory failure were studied, with a gestational age (GA) ≤ 36 weeks and birth weight (BW) > 750 g, who required tracheal intubation and mechanical ventilation. The study was controlled and randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
1
14
0
3
Order By: Relevance
“…Furthermore, we did not detect significant differences in the rates of neonatal morbidities including sepsis, pneumothorax, IVH, ROP, BPD, BPD/death rates or mortality between the groups. Nonetheless, consistent with the study of Komatsu et al (6) , the incidence of hsPDA was higher in the NIPPV group, compared to the NCPAP group in our study. hsPDA was defined as the ductus arteriosus having a diameter of ≥1.5 mm and a ratio of ≥1.5 between the size of the left atrium and the diameter of the aortic root and diastolic reversal of blood flow in the aorta on portable echocardiography (30) .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, we did not detect significant differences in the rates of neonatal morbidities including sepsis, pneumothorax, IVH, ROP, BPD, BPD/death rates or mortality between the groups. Nonetheless, consistent with the study of Komatsu et al (6) , the incidence of hsPDA was higher in the NIPPV group, compared to the NCPAP group in our study. hsPDA was defined as the ductus arteriosus having a diameter of ≥1.5 mm and a ratio of ≥1.5 between the size of the left atrium and the diameter of the aortic root and diastolic reversal of blood flow in the aorta on portable echocardiography (30) .…”
Section: Discussionsupporting
confidence: 93%
“…In the literature, gastrointestinal complications such as abdominal distension, feeding intolerance, NEC, and intestinal perforation did not differ between the neonates assigned to NIPPV or NCPAP following extubation (6,11,(21)(22)(23) . Although there is a limited number of data on abdominal distension and feeding intolerance in our study, intestinal perforation was not observed in any of the infants.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Ten studies were adjudged as having a high risk of bias due to issues in random sequence generation and allocation concealment. 30,32,33,39,40,[43][44][45]47,53 Eight studies had a low risk of bias 21,23,25,26,42,48,50,52 and fifteen studies had variable risk of bias. 22,24,[27][28][29]31,[34][35][36][37][38]41,46,49,51 Due to the nature of the intervention, blinding of the personnel and outcome assessor was not possible and hence all the trials scored a high risk of bias for the same.…”
Section: Risk Of Bias Of the Included Studiesmentioning
confidence: 99%